Conformation sensitive gel electrophoresis for the detection of calreticulin mutations in BCR‐ABL1‐negative myeloproliferative neoplasms. (14th June 2021) - Zakaria, Nur Atikah; Rosle, Norfifiana Alisa; Siti Asmaa, Mat Jusoh; Aziee, Sudin; Haiyuni, Mohd Yassim; Samat, Nurul Ameera; Husin, Azlan; Hassan, Rosline; Ramli, Marini; Mohamed Yusoff, Shafini; Ibrahim, Ibrahim Khidir; Al‐Jamal, Hamid Ali Nagi; et al.
Abstract: Introduction: Calreticulin ( CALR ) mutations in myeloproliferative neoplasms (MPN) have been reported to be key markers in the molecular diagnosis, particularly in patients lacking JAK2 V617F mutation. In most current reports, CALR mutations were analysed by either allele‐specific PCR (AS‐PCR), or the more expensive quantitative real‐time PCR, pyrosequencing and next‐generation sequencing. Hence, we report the use of an alternative method, the conformation sensitive gel electrophoresis (CSGE) for the detection of CALR mutations in BCR‐ABL1 ‐negative MPN patients. Methods: Forty BCR‐ABL1 ‐negative MPN patients' DNA: 19 polycythemia vera (PV), 7 essential thrombocytosis (ET) and 14 primary myelofibrosis (PMF), were screened for CALR mutations by CSGE. PCR primers were designed to amplify sequences spanning between exons 8 and 9 to target the mutation hotspots in CALR . Amplicons displaying abnormal CSGE profiles by electrophoresis were directly sequenced, and results were analysed by BioEdit Sequence Alignment Editor v7.2.6. CSGE results were compared with AS‐PCR and confirmed by Sanger sequencing. Results: CSGE identified 4 types of mutations; 2 PMF patients with either CALR type 1 (c.1099_1150del52) or type 2 (c.1155_1156insTTGTC), 1 ET patient with nucleotide deletion (c.1121delA) and insertion (c.1190insA) and 1 PV patient with p.K368del (c.1102_1104delAAG) and insertion (c.1135insA) inframe mutations. Three patients have an altered KDEL motif at the C‐terminal of CALR protein. In comparison, AS‐PCR only able to detect two PMF patients with mutations, either type 1 and type 2. Conclusion: CSGE is inexpensive, sensitive and reliable alternative method for the detection of CALR mutations in BCR‐ABL1 ‐negative MPN patients.